ANALYSIS OF QUALITY CONTROL FOR A DISC RIDGER EMPLOYED FOR A YELLOW-RED CLAY SOIL - Melo, R. P.; Albiero, D.; Praciano, A. C.; Cavalcante, E. S.; Fernandes, F. R. B. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The ridger is an agricultural implement employed for forming ridges on the soil, which aims to control the flow of rainwater and allowing a better water retention in the soil, therefore the cutting angle of the ridger must be adjusted according to the soil where it is being worked, for the highest efficiency on ridges shaping. The purpose of this work was to evaluate the quality control of a ridger operating in different cutting angles through the Statistical Process Control techniques. The study was performed in a Yellow-Red Clay Soil and the cutting angles of the ridger were 90 °, 100 ° and 110 °. A ​​50 m distance was demarcated for the assay. For data collection, we measured the larger base, smaller base and the height of slope. The quality control for the rigder was evaluated by the statistical process control with the different cutting angles. The software Minitab – Version 16 was employed for the data analysis. The angle of 90° had the best performance, however, it is needed to verify the process due to a high variability of samplings within the specified limits.